A Light‐Driven Molecular Machine Controls K+ Channel Transport and Induces Cancer Cell Apoptosis. (3rd May 2022) - Yang, Huiting; Yi, Jinhao; Pang, Shihao; Ye, Kai; Ye, Zhicheng; Duan, Qi; Yan, Zexin; Lian, Cheng; Yang, Yi; Zhu, Linyong; Qu, Da‐Hui; Bao, Chunyan
Abstract: The design of artificial ion channels with high activity, selectivity and gating function is challenging. Herein, we designed the light‐driven motor molecule MC2, which provides new design criteria to overcome these challenges. MC2 forms a selective K + channel through a single molecular transmembrane mechanism, and the light‐driven rotary motion significantly accelerates ion transport, which endows the irradiated motor molecule with excellent cytotoxicity and cancer cell selectivity. Mechanistic studies reveal that the rotary motion of MC2 promotes K + efflux, generates reactive oxygen species and eventually activates caspase‐3‐dependent apoptosis in cancer cells. Combined with the spatiotemporally controllable advantages of light, we believe this strategy can be exploited in the structural design and application of next‐generation synthetic cation transporters for the treatment of cancer and other diseases. Abstract : Inspired by the functions of biological motors, a light‐driven motor molecule was designed that inserts into the lipid membrane and transports ions with high ion selectivity and gating function. The light‐driven motor rotation accelerates K + efflux and induces caspase‐dependent apoptosis of cancer cells.